Failure analysis of damages on advanced technologies induced by picosecond pulsed laser during space radiation SEE testing - Chua, C. T. (2019)
Picosecond pulsed laser, customarily perceived to offer advantages of flexibility and ease of testing over heavy ion particle accelerator test, was conducted on a chain of inverters during Single Event Effect (SEE) evaluation. In this paper, we report on the unexpected permanent damage induced by 1064 nm pulsed laser on test structures fabricated with 65 nm bulk CMOS process technology. Light emission microscopy (EMMI) localized hotspots within the area previously scanned by the pulsed laser. Electro Optical Frequency Mapping (EOFM) verified the undesired termination of signal propagation along the chain of inverters while Electro Optical Probing (EOP) confirmed the unexpected phase change and eventual loss of the output signal waveform. Focused Ion Beam (FIB), Transmission Microscopy (TEM) and Energy Dispersive X-ray spectroscopy (EDX) confirmed the physical failure and identified nickel as the diffusing species. This paper aims to advise caution to the research communities (both space radiation and optical failure analysis) in employing similar laser test technique and highlights the need to define the safe operating region of such technique, especially for emerging technology nodes.